2020
DOI: 10.1371/journal.pbio.3000941
|View full text |Cite
|
Sign up to set email alerts
|

YAP/TAZ deficiency reprograms macrophage phenotype and improves infarct healing and cardiac function after myocardial infarction

Abstract: Adverse cardiac remodeling after myocardial infarction (MI) causes structural and functional changes in the heart leading to heart failure. The initial post-MI pro-inflammatory response followed by reparative or anti-inflammatory response is essential for minimizing the myocardial damage, healing, and scar formation. Bone marrow–derived macrophages (BMDMs) are recruited to the injured myocardium and are essential for cardiac repair as they can adopt both pro-inflammatory or reparative phenotypes to modulate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 90 publications
7
88
0
Order By: Relevance
“…Expression of Hippo signaling pathway components such as Yap, Tead1, Tead2, Tead3, Amot, and Axin2 was significantly decreased in BAF155/170-deficient (Wnt1 Cre/ + ;BAF155 fl/fl ;BAF170 fl/fl ) NCCs. Hippo signaling pathway is a highly conserved pathway that regulates cellular proliferation, differentiation, and survival [55][56][57][58][59][60][61]. The downstream effector's Yap and Taz interact with transcription factors including Tead1-4 to promote migration, proliferation, and differentiation of NCCs in different biological systems.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Expression of Hippo signaling pathway components such as Yap, Tead1, Tead2, Tead3, Amot, and Axin2 was significantly decreased in BAF155/170-deficient (Wnt1 Cre/ + ;BAF155 fl/fl ;BAF170 fl/fl ) NCCs. Hippo signaling pathway is a highly conserved pathway that regulates cellular proliferation, differentiation, and survival [55][56][57][58][59][60][61]. The downstream effector's Yap and Taz interact with transcription factors including Tead1-4 to promote migration, proliferation, and differentiation of NCCs in different biological systems.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…used 3D micropores and 2D micropatterns to limit the spread of macrophages, which inhibited the inflammatory gene expression profile by reducing actin polymerization [ 53 ]. Evidence further showed that YAP (a mediator of mechanotransduction) could reprogram macrophage phenotypes in many diseases [ [54] , [55] , [56] ]. The results in this study indicated that YAP activity might be related to stiffness, and inhibition of actin-mediated nuclear translocation of YAP had the potential for inflammatory suppression.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and mortality of HF are high, and it endangers the health of patients with cardiovascular and cerebrovascular diseases ( 18 ). Myocardial infarction is the main cause of HF ( 19 ). It is well known that cardiomyocytes are not renewable.…”
Section: Discussionmentioning
confidence: 99%